Case Report: Autoimmune polyglandular syndrome type 4 involving diabetes mellitus type 1, autoimmune hepatitis, immune thrombocytopenia, and celiac disease - Nesterowicz, Miłosz; Anikiej, Katarzyna; Borysewicz-Sańczyk, Hanna; Zasim, Aneta; Trzebuchowski, Stanisław; Bąbol-Pokora, Katarzyna; Lebensztejn, Dariusz; Leszczyńska, Elżbieta; Bossowski, Artur (Frontiers in Endocrinology, 2025)
Autoimmune polyglandular syndromes refer to a group of disorders characterized by dysfunction in two or more endocrine glands, often accompanied by autoimmune involvement in non-endocrine tissues. A 6-year-old girl was admitted due to suspected diabetes mellitus. The symptoms observed by the parents were polyuria, polydipsia, and an acetone odor. Physical examination revealed a dry oral mucosa, a tongue coated with a white film, ecchymoses on the upper limbs, and a distended abdomen, arched above the chest level, and increased bowel sounds. After comprehensive differential diagnostics, the patient was identified with diabetes mellitus type 1, autoimmune hepatitis, immune thrombocytopenia, celiac disease, and thus autoimmune polyglandular syndrome type 4. The case illustrates a very rare combination of coexisting autoimmune disorders. When a patient is diagnosed with one autoimmune disease, it is crucial to screen actively for other autoimmune conditions. It is essential to remember that the clinical presentation of a patient is often the result of overlapping symptoms from multiple conditions.